The Effect Of Msib Internship Experience And Competence On Work Readiness Of Upn "Veteran” Jawa Timur Management Students - Prakusya, Diva Yunieq; Irbayuni, Sulastri (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study is motivated by the increasing importance of work readiness among university graduates in facing global competition. Work readiness reflects the extent to which graduates can adapt and meet workplace demands. This research aims to examine the influence of MSIB internship experience and competence on the work readiness of Management students at UPN “Veteran” Jawa Timur. A quantitative approach was used in this study with a sample of 43 students from the 2021 cohort who had participated in the MSIB program. Data were collected using questionnaires and analyzed through SmartPLS. The results showed that internship experience and competence contribute to students’ work readiness.